Performance and Ethics: Levers of Scientific Research Reform in Morocco - EL AZZOUZI , Nihale; MAKHROUTE , Mohamed; OUALD EL HAJ , Asmae (Revue du contrôle, de la comptabilité et de l’audit, 2022)
This contribution deals with Performance-Based Management related to the reform of Morocco’s Education, Training, and Scientific Research system, focusing on the Scientific Research component. In fact, Public finance has become a major instrument of public policy, and a vital means for public authorities to direct and develop economic and social life, so for good public financial governance, the management of public finances must obey ethical rules based on principles of integrity, transparency, accountability and equity. Furthermore, the administrative reform undertaken around the modernization of public management and the search for links between performance and ethics has become a central concern of managers and theorists. The objective is therefore to present a theoretical overview of the concepts of performance and ethics and the relationship between them in the context of public management, then focus on the monitoring of the performance of scientific research and present the main strategic visions of the sector and the integration of ethics by the new model of development.